Visualizations for computer graphics concepts - Khairuddin Ali (Nanyang Technological University, 2022)
ShapeExplorer is a tool created to perform function-based shape modelling and visualization. It is provided to students in NTU as part of the Computer Graphics and Visualization coursework project, and other related studies. ShapeExplorer can only be run on desktop operating systems. Performance in mobile devices is increasing and they should be powerful enough to run a ShapeExplorer-like program. A web application was developed to explore mobile device’s capability in running a ShapeExplorer-like program while maintaining compatibility with desktop platforms. It was written in Javascript, using React and Material UI libraries to build its user interface and three.js, a lightweight 3D library, to generate and display 3D shapes. Parametric functions are parsed differently in this application compared to ShapeExplorer. Instead of interpreting the functions as code, they are parsed into tokens that are evaluated to generate each point in the 3D shape. The web application was able to successfully create curves, surfaces, and solids using parametric functions and display them onto a virtual scene. It only has 2 features of ShapeExplorer, parametric shape generation and loading of examples, so more work can be done to reach feature parity.